Rapid three dimensional two photon neural population scanning - Schuck,R; Quicke,P; Hwang,JK; Annecchino,L; Schultz,SR (IEEE, 2015)
Recording the activity of neural populationsat high sampling rates is a fundamental requirement forunderstanding computation in neural circuits. Two photonmicroscopy provides one promising approach towards this.However, neural circuits are three dimensional, and functionalimaging in two dimensions fails to capture the 3D natureof neural dynamics. Electrically tunable lenses (ETLs) providea simple and cheap method to extend laser scanningmicroscopy into the relatively unexploited third dimension.We have therefore incorporated them into our Adaptive SpiralScanning (SSA) algorithm, which calculates kinematicallyefficient scanning strategies using radially modulated spiralpaths. We characterised the response of the ETL, incorporatedits dynamics using MATLAB models of the SSA algorithmand tested the models on populations of Izhikevich neuronsof varying size and density. From this, we show that ouralgorithms can theoretically at least achieve sampling rates of36.2Hz compared to 21.6Hz previously reported for 3D scanningtechniques.